2020
DOI: 10.1080/20013078.2020.1763594
|View full text |Cite
|
Sign up to set email alerts
|

The αvβ6 integrin in cancer cell‐derived small extracellular vesicles enhances angiogenesis

Abstract: Prostate cancer (PrCa) cells crosstalk with the tumour microenvironment by releasing small extracellular vesicles (sEVs). sEVs, as well as large extracellular vesicles (LEVs), isolated via iodixanol density gradients from PrCa cell culture media, express the epithelial-specific αvβ6 integrin, which is known to be induced in cancer. In this study, we show sEV-mediated protein transfer of αvβ6 integrin to microvascular endothelial cells (human microvascular endothelial cells 1-HMEC1); we demonstrate that de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Our previous study demonstrates that the dysregulated expression of the αVβ3 integrin in small extracellular vesicles released by PrCa cells promotes a shift in lineage plasticity towards a NE lineage [ 7 ]. Moreover, although our group has reported that the αVβ6 integrin, in small extracellular vesicles released by cancer cells, induces M2 polarization in recipient monocytes [ 64 ] and stimulates angiogenesis in endothelial cells during cancer progression [ 65 ], is absent in NEPrCa. Here we show that the αVβ3 integrin is upregulated in tumor samples from patients affected by NEPrCa and in corresponding NE murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrates that the dysregulated expression of the αVβ3 integrin in small extracellular vesicles released by PrCa cells promotes a shift in lineage plasticity towards a NE lineage [ 7 ]. Moreover, although our group has reported that the αVβ6 integrin, in small extracellular vesicles released by cancer cells, induces M2 polarization in recipient monocytes [ 64 ] and stimulates angiogenesis in endothelial cells during cancer progression [ 65 ], is absent in NEPrCa. Here we show that the αVβ3 integrin is upregulated in tumor samples from patients affected by NEPrCa and in corresponding NE murine models.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of EV biomarkers for cancer prognostics was also discussed as cancer EVs are reported to carry distinct integrin profiles, which is associated with their preferential metastatic site [56] and functionally relevant [57,58]. Other biomarkers are currently being developed to predict clinical outcomes, such as the EV‐derived PD‐L1 has been suggested as a predictor for the clinical outcomes of anti‐PD‐1 therapy [59] and EV‐tethered TGF‐β had previously shown promise to predict response to HER2‐targeted drugs [60].…”
Section: Ev Biomarker Detection and Application In Clinical Diagnosismentioning
confidence: 99%
“…Recent data indicate that integrins in cancer cell EVs may also regulate tumor-induced angiogenesis. Integrin αvβ6-containing EVs released by prostate cancer cells mediate αvβ6 transfer to microvascular endothelial cells and promote endothelial cell motility and tube formation, in contrast to EVs isolated from β6 negative cancer cells [ 77 ]. Finally, integrins can regulate the sorting of fibronectin into cancer cell EVs, as well as the contents and antibacterial activity of neutrophil EVs, although how integrins crosstalk with the sorting machinery remains to be established [ 75 , 78 ].…”
Section: Integrins Control Uptake Of Extracellular Vesicles and Virusmentioning
confidence: 99%